A surface protease of Lyme disease bacteria degrades host extracellular matrix components and induces inflammatory cytokines in vitro - Russell, Theresa Michelle Tidd, author; Bamburg, James R., advisor; Johnson, Barbara J. B., advisor; Luger, Karolin, committee member; Cohen, Robert E., committee member; Gentry-Weeks, Claudia, committee member (Colorado State University. Libraries, 2012)
For nearly two decades, the paradigm in Lyme disease research has been that Borrelia burgdorferi does not produce proteases capable of damaging host molecules. Lyme disease has been considered, therefore, to be the consequence of an exuberant inflammatory response to infecting bacteria. This prevailing concept, however, has created a conundrum for the field. The bacterial burden in infected tissue is low, but the degree of inflammation is remarkable and seemingly out of proportion to this burden. The studies described in this dissertation provide evidence that, contrary to current thinking, B. burgdorferi does possess a protease that degrades numerous molecules of the host extracellular matrix (ECM). In addition to destabilization of the ECM which would be expected to benefit the organism, characterization of this proteolytic activity demonstrates that ECM fragments are produced that are known to be pro-inflammatory. These bioactive fragments may amplify the inflammatory processes triggered by the presence of the bacteria itself. When this hypothesis was tested directly by exposing chondrocytes to the borrelial protease in vitro, inflammatory cytokines and chemokines that are hallmarks of Lyme disease were induced. The studies herein suggest a new model for the pathogenesis of Lyme disease and offer an explanation for the paradox of debilitating inflammatory disease in the presence of few infecting organisms. Lastly, in contrast to current serology-based Lyme disease diagnostic tests, the activity of this protease in vitro may generate diagnostic biomarkers enabling detection of active B. burgdorferi infection.
Keywords: BB0104; BbHtrA; cytokine/chemokine; Lyme; protease; proteoglycan